Pediatras e os distúrbios respiratórios do sono na criança - Balbani, Aracy Pereira Silveira [UNESP]; Weber, Silke Anna Thereza [UNESP]; Montovani, Jair Cortez [UNESP]; De Carvalho, Lídia Raquel [UNESP] (My University, 2005)
OBJECTIVES. assessment of opinions and practices of pediatricians concerning sleep-disordered breathing (SDB) in children. Methods. randomly 516 pediatricians were selected in the state of São Paulo, Brazil. A survey mailed to them included questions regarding: their professional profile, knowledge about SDB in childhood, opinions and practices for diagnosis and treatment of these diseases. RESULTS. 112 anonymous completed surveys were returned (21.7%). The teaching of SDB during medical school and pediatric residency training was considered unsatisfactory respectively by 65.2% and 34.8% of the pediatricians. Forty-nine respondents (43.8%) rated their knowledge about SDB in children as regular, 39 (34.8%) as good and 17 (15.2%) as unsatisfactory. The most important sleep-related questions were: mouth breathing, breathing pauses, sleep amount, excessive daytime sleepiness and nocturnal wheezing. Clinical aspects regarded as the most significant for suspecting obstructive sleep apnea syndrome (OSAS) were: breathing pauses, adenoid hypertrophy, mouth breathing, craniofacial anomaly and snoring. The most frequent practices for evaluation of OSAS in children were: cavum radiography with referral to an otorhinolarnygologist (25%) and nocturnal pulse oximetry (14.2%). Only 11.6% of pediatricians recommended overnight polysomnography and 4.5%, nap polysomnography. The most effective practices for SDB were considered to be: adenoidectomy and adenotonsillectomy, parents counseling, weight loss and sleep hygiene. CONCLUSIONS. there is a gap between research on SDB in childhood and pediatric practice. © 2006 Associação Médica Brasileira.
Pediatricians and sleep-disordered breathing in the child
Keywords: Child; Medical education; Obstructive sleep apnea; Snoring